Evaluation of breast cancer knowledge, beliefs, and self-examination practices among female college teachers in Pakistan - Mahar, Benazir; Osman, Malina; Ahmad Fauzi, Fatimah; Hod, Rafidah; Shah, Tazeen (Wolters Kluwer Medknow Publications, 2025)
Background: Breast cancer (BC) is a prevalent malignancy in women, and breast self-examination (BSE) is an important tool for early diagnosis. Despite its significance, BSE is insufficiently practiced, particularly in developing countries. This research evaluated the knowledge, beliefs, and practices concerning breast cancer and breast self-examination among female college teachers in Pakistan. Materials and Methods: A cross-sectional study was conducted in August 2024, using the health belief model (HBM) as a theoretical framework, involving 176 female college teachers in Hyderabad, Pakistan. A validated questionnaire was employed for data acquisition. Descriptive and inferential statistics, including regression analysis, were used to determine predictors. Results: Only 13.6% of the individuals indicated consistent breast self-examination (BSE) engagement. The median knowledge score was 12, with an interquartile range of 5. Regression analysis revealed that marital status, level of education, family history of breast cancer, history of benign breast diseases, and having a health professional in the family were significant predictors of knowledge, beliefs, and BSE practices (P < 0.05). Conclusion: There is a notable gap in awareness and regular BSE performance among respondents. To improve BSE practices, targeted strategies, including educational interventions for teachers, are crucial.